2023
DOI: 10.1021/jacs.3c01574
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant Micellar and Vesicle Microenvironments and Structures under Synthetic Organic Conditions

Abstract: Fluorescence lifetime imaging microscopy (FLIM) reveals vesicle sizes, structures, microenvironments, reagent partitioning, and system evolution with two chemical reactions for widely used surfactant–water systems under conditions relevant to organic synthesis, including during steps of Negishi cross-coupling reactions. In contrast to previous investigations, the present experiments characterize surfactant systems with representative organohalide substrates at high concentrations (0.5 M) that are reflective of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 63 publications
0
23
0
Order By: Relevance
“…These results further confirmed that the addition of TMB caused morphological changes in the micelles. It was mainly due to the hydrophobic interaction that drives TMB into the hydrophobic cavity of SDS micelles. , Moreover, from a kinetic point of view, such a confined space would improve the local concentration of reactants and accelerate the oxidation reaction rate, i.e., making TMB be in an “activated” state. To confirm this assumption, the TMB oxidation in aqueous solution with and without SDS micelles was explored under light irradiation that would photochemically produce a trace amount of free ROS.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These results further confirmed that the addition of TMB caused morphological changes in the micelles. It was mainly due to the hydrophobic interaction that drives TMB into the hydrophobic cavity of SDS micelles. , Moreover, from a kinetic point of view, such a confined space would improve the local concentration of reactants and accelerate the oxidation reaction rate, i.e., making TMB be in an “activated” state. To confirm this assumption, the TMB oxidation in aqueous solution with and without SDS micelles was explored under light irradiation that would photochemically produce a trace amount of free ROS.…”
Section: Resultsmentioning
confidence: 99%
“…In stage II (from 400 to 1200 s), a gradual decrease in the scattering intensity was observed, indicating the oxidation of TMB and the departure of the oxidation product from the SDS micelles. Due to the positive electrical and hydrophilic nature of the oxidation products, the oxidation products would move to the outer surface of the micelles that was hydrophobic and negatively charged properties . To verify this assumption, the ζ-potential of the mixed solution of SDS micelles (10 mM) and TMB (0.05 mM) was determined to be −61.55 ± 1.14 mV, while the ζ-potential of the solution changed to −37.43 ± 1.65 mV after the addition of H 2 O 2 (100 mM).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As part of sustainability, contemporary analytical chemistry has developed miniaturized and eco-friendly analytical methods employing biodegradable and green solvents . Unique microenvironments provided by surfactant micellar structures have been explored in green organic synthesis, for the development of nanostructured hydrogel materials, for developing micelles with responsive emission, FRET-enabled micelles for nucleic acid detection, and even to attain aqueous sensing of biorelevant anions . Similarly, the tailored supramolecular solvent (SUPRAS) is stepping sustainability ahead and these solvents find application in separation techniques, such as liquid–liquid extraction and chromatography, due to their ability to selectively solvate desired molecules .…”
Section: Introductionmentioning
confidence: 99%
“…12 In addition, such chemistry tends to happen with reprotoxic polar aprotic solvents, such as DMA, DMF or NMP, 13 which are not preferred due to the tedious purification processes they necessitate, on top of their now well-recognized sustainability drawbacks. 14 Meanwhile, chemistry-in-water technology has become more and more popular owing to the demand of reducing the environmental footprint, 15 as one example demonstrated by Lipshutz and co-workers in 2009, who reported a palladium-catalyzed aryl–alkyl cross coupling under micellar conditions. 16…”
mentioning
confidence: 99%